The analysis of fluid flow on different kapok filter orientations using computer fluid dynamics / Ab Aziz Mohd Yusof ... [et al.] - Mohd Yusof, Ab Aziz; Hambali, Norhafini; Abdullah, Mohammad; Ismail, Nur Darina; Samsudin, Azizul Hakim (Smart Manufacturing Research Institute (SMRI), 2023)
Kapok fibres, known for their hydrophobic (water-repellent) and oleophilic (oil-attracting) properties, could be used as a filtration medium. In the context of oily water filtration, kapok fibres might naturally attract and capture oil droplets from the water while allowing water to pass through. However, the effectiveness of the filtering process depends on the filter orientation, which affects the fluid flow, either turbulent or laminar. Thus, the study investigated the effect of filter orientation housing during installation on the fluid flow around the kapok filter. The study used Computational fluid dynamic analysis, CFD, for two different kapok filter orientations, parallel and perpendicular to the water flow. It found that the kapok filter oriented perpendicular generates turbulence on the surrounding flow and hydraulic jump as compared to parallel orientation. A higher risk of clogging could happen due to debris accumulation and reduced filtering process.